ASEAN+1 FTAs and the Global Supply Chain in East Asia: the Case of the Philippine Automotive and Electronics Sectors - Erlinda M. Medalla; Maureen Ane D. Rosellon (Philippine Institute for Development Studies (PIDS), 2012)
How are the ASEAN+1 free trade agreements facilitating the flow of goods in the supply chain in East Asia? This chapter looks at the experience of the Philippine automotive and electronic sectorsâ-two sectors that are well integrated into the supply network in East Asia. Using firm interviews, the study outlines the firms' segment of the supply chain and identifies impediments at points critical for firms, particularly in relation to free trade agreements. FTA utilization and awareness, trade facilitation, logistics and government support are some of the issues that come to light.
Keywords: 330; Philippines; supply chain; value chain; East Asia; ASEAN Free Trade Agreement (AFTA); Philippine automotive and electronics sectors